High-nitrogen nickel-saving stainless steel casting powder and preparation process thereof

By using deoxidant prepared by germanium tetrachloride and N,N'-diphenylguanidine in high-nitrogen nickel stainless steel protective slag, the problem of deoxygenation is solved, the purity of the steel liquid and the quality of the casting billet are improved, and the quality of the casting billet is achieved. Stable deoxygenation effect and fluidity.

CN119259933AInactive Publication Date: 2025-01-07LUO YANG SHI KE FENG YE JIN XIN CAI LIAO YOU XIAN GONG SI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411815852.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The deoxidant in the existing high-nitrogen nickel stainless steel protective slag causes uneven deoxygenation due to rapid deoxygenation, which affects the purity and tissue uniformity of the stainless steel and reduces its performance.

Method used

Deoxidant prepared in a certain proportion of germanium tetrachloride and N,N'-diphenylguanidine, absorbs oxygen in the steel liquid through germanium, and uses N,N'-diphenylguanidine to decompose and produce gas at high temperature. , improve the fluidity and dispersion of the protective slag, control the stable release of deoxidants, and avoid oxide aggregation and contamination caused by rapid release.

Benefits of technology

The consistency of the liquid steel composition is achieved, the surface quality of the casting billet and the deoxygenation performance of the protective slag is improved, oxide pollution is avoided, and the uniformity and fluidity of the protective slag are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of casting powder preparation, in particular to high-nitrogen nickel-saving stainless steel casting powder and a preparation process thereof. The invention discloses a high-temperature-resistant ceramic material which comprises the following components in parts by weight: 1-5 parts of a deoxidizing agent, 35-45 parts of calcium oxide, 14-24 parts of silicon dioxide, 6-14 parts of aluminum oxide, 7-11 parts of calcium fluoride, 2-4 parts of magnesium oxide, 2-6 parts of lithium oxide, 3-5 parts of iron monoxide, 1-3 parts of titanium dioxide, 2-6 parts of nano zirconium oxide and 2-10 parts of cetyltrimethylammonium bromide. Wherein the deoxidizing agent is prepared from germanium tetrachloride and N, N '-diphenyl guanidine according to the mass ratio of 1: (1.5-2), the deoxidizing agent obtained by adopting a complex of the germanium tetrachloride and the N, N'-diphenyl guanidine can absorb oxygen in molten steel, promote dispersity of casting powder and control the deoxidizing effect at the same time, and the situation that due to the fact that the deoxidizing agent is rapidly released, a large number of oxides are gathered in a short time, and the deoxidizing effect is affected is avoided. And the phenomenon that molten steel is polluted due to upward floating and discharging is avoided, so that the surface quality of a casting blank is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of protective slag preparation, and in particular to a high-nitrogen nickel-saving stainless steel protective slag and a preparation process thereof. Background Art

[0002] High-nitrogen nickel-saving stainless steel is a new type of stainless steel material with unique composition and excellent performance. It is increasingly used in the field of stainless steel, especially in situations where high strength, high corrosion resistance and cost-effectiveness are equally important. This material achieves significant optimization of material properties by adding a higher proportion of nitrogen to stainless steel and appropriately reducing the nickel content. It also opens up new ways for the rational use of resources and cost reduction. From petrochemicals, marine engineering to food processing and medical equipment, high-nitrogen nickel-saving stainless steel is driving the continuous innovation and development of stainless steel material applications with its unique advantages.

[0003] However, the deoxidizer in the existing protective slag causes uneven deoxidation due to rapid deoxidation, resulting in a high oxygen content in some areas, while other areas may be over-deoxidized. At the same time, during the rapid deoxidation process, the deoxidizer reacts rapidly with the oxygen in the stainless steel melt to generate a large number of inclusions, which seriously affect the purity and organizational uniformity of the stainless steel, thereby reducing its performance. In view of this, we propose a high-nitrogen nickel-saving stainless steel protective slag and its preparation process. Summary of the invention

[0004] The object of the present invention is to provide a high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] To achieve the above object, the present invention provides a high-nitrogen nickel-saving stainless steel protective slag, comprising the following components: 1-5 parts by weight of a deoxidizer, 35-45 parts by weight of calcium oxide, 14-24 parts by weight of silicon dioxide, 6-14 parts by weight of aluminum oxide, 7-11 parts by weight of calcium fluoride, 2-4 parts by weight of magnesium oxide, 2-6 parts by weight of lithium oxide, 3-5 parts by weight of iron oxide, 1-3 parts by weight of titanium dioxide, 2-6 parts by weight of nano zirconium oxide and 2-10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:1.5-2.

[0006] Preferably, the preparation method of the deoxidizer is as follows: Dissolve germanium tetrachloride in ethanol solvent, stir well, heat the solution to 75-78°C, add dilute hydrochloric acid solution to adjust the pH value, then add N,N'-diphenylguanidine three times, and continue stirring for 4-6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer.

[0007] Germanium can absorb oxygen in the molten steel and act as a deoxidizer, thereby improving the continuous casting speed and the surface quality of the ingot. N,N'-diphenylguanidine can decompose at high temperatures to produce gases such as carbon dioxide. The generation of gases helps to improve the fluidity of the protective slag and the uniform mixing of the slag system. After N,N'-diphenylguanidine is coordinated with germanium, it can increase the distance between the complexes through electrostatic repulsion or steric hindrance effect, thereby improving its dispersibility in the protective slag. In addition, the complex gradually produces germanium due to the rupture of coordination bonds at high temperatures. At this time, the complex can control its decomposition rate at high temperatures, so that the germanium element can be released at a relatively stable rate instead of all at once, avoiding the phenomenon that a large amount of oxides gather in a short time when the deoxidizer is released quickly, which is not easy to float up and discharge, but pollutes the molten steel. The activity of the deoxidizer is controlled, and the deoxidation effect of the protective slag is slowly adjusted, which helps to maintain the consistency of the composition of the molten steel.

[0008] Preferably, the mass concentration of the germanium tetrachloride solution is 20-40 g / L.

[0009] Preferably, the molar concentration of the dilute hydrochloric acid solution is 0.1-0.5 M, and the pH of the solution is adjusted to 3-5.

[0010] On the other hand, the present invention provides a process for preparing a high-nitrogen nickel-saving stainless steel protective slag, which is used for a high-nitrogen nickel-saving stainless steel protective slag as described in any one of the above, comprising the following steps: The nano zirconium oxide is added to the hexadecyltrimethylammonium bromide solution, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain the surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set at 100-110°C. The dried protective slag is crushed, ground and sieved to obtain the protective slag.

[0011] Preferably, the particle size range of the raw material subjected to preliminary grinding is 0.01-0.1 mm.

[0012] Preferably, the molar concentration of the hexadecyltrimethylammonium bromide solution is 1-10M.

[0013] Preferably, the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1 to 1.5.

[0014] Hexadecyltrimethylammonium bromide, as a surfactant, can change the surface properties of nanomaterials, improve their adsorption capacity and catalytic performance, and add surfactant-modified nano-zirconia to the protective slag to improve the adsorption performance of surfactant-modified nano-zirconia for deoxidizers and iron monoxide, thereby improving the stability of deoxidizers and iron monoxide, and better exerting their deoxidation effect in high temperature environments.

[0015] Preferably, the moisture content of the protective slag is less than 2%.

[0016] Preferably, the particle size of the protective slag is 0.05-0.3 mm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: In the high-nitrogen nickel-saving stainless steel protective slag and its preparation process, a complex of germanium tetrachloride and N,N'-diphenylguanidine is used as a deoxidizer, which can not only absorb oxygen in molten steel to prevent oxidation of the molten steel, but also utilize N,N'-diphenylguanidine to decompose and generate gas at high temperature, thereby improving the fluidity of the protective slag and the uniform mixing of the slag system, and at the same time, can control the stable deoxidation efficiency of the deoxidizer, avoid the phenomenon that a large amount of oxides are not easy to float up and discharge due to the rapid release of the deoxidizer, but pollute the molten steel, help maintain the consistency of the molten steel composition, and thus improve the surface quality of the ingot. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0019] The invention discloses a high-nitrogen nickel-saving stainless steel protective slag, comprising the following components: 1-5 parts by weight of a deoxidizer, 35-45 parts by weight of calcium oxide, 14-24 parts by weight of silicon dioxide, 6-14 parts by weight of aluminum oxide, 7-11 parts by weight of calcium fluoride, 2-4 parts by weight of magnesium oxide, 2-6 parts by weight of lithium oxide, 3-5 parts by weight of iron oxide, 1-3 parts by weight of titanium dioxide, 2-6 parts by weight of nano zirconium oxide and 2-10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:1.5-2.

[0020] Embodiment 1: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 1 part by weight of deoxidizer, 45 parts by weight of calcium oxide, 24 parts by weight of silicon dioxide, 14 parts by weight of aluminum oxide, 11 parts by weight of calcium fluoride, 4 parts by weight of magnesium oxide, 6 parts by weight of lithium oxide, 5 parts by weight of iron oxide, 3 parts by weight of titanium dioxide, 6 parts by weight of nano zirconium oxide and 10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:2; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1.5; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0021] Embodiment 2: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 3 parts by weight of deoxidizer, 45 parts by weight of calcium oxide, 24 parts by weight of silicon dioxide, 14 parts by weight of aluminum oxide, 11 parts by weight of calcium fluoride, 4 parts by weight of magnesium oxide, 6 parts by weight of lithium oxide, 5 parts by weight of iron oxide, 3 parts by weight of titanium dioxide, 6 parts by weight of nano zirconium oxide and 10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:2; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1.5; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0022] Embodiment 3: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 5 parts by weight of deoxidizer, 45 parts by weight of calcium oxide, 24 parts by weight of silicon dioxide, 14 parts by weight of aluminum oxide, 11 parts by weight of calcium fluoride, 4 parts by weight of magnesium oxide, 6 parts by weight of lithium oxide, 5 parts by weight of iron oxide, 3 parts by weight of titanium dioxide, 6 parts by weight of nano zirconium oxide and 10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:2; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1.5; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0023] Example 4: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 1-5 parts by weight of deoxidizer, 35 parts by weight of calcium oxide, 14 parts by weight of silicon dioxide, 6 parts by weight of aluminum oxide, 7 parts by weight of calcium fluoride, 2 parts by weight of magnesium oxide, 2 parts by weight of lithium oxide, 3 parts by weight of iron oxide, 1 part by weight of titanium dioxide, 2 parts by weight of nano zirconium oxide and 2 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:2; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0024] Example 5: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 3 parts by weight of deoxidizer, 45 parts by weight of calcium oxide, 24 parts by weight of silicon dioxide, 14 parts by weight of aluminum oxide, 11 parts by weight of calcium fluoride, 4 parts by weight of magnesium oxide, 6 parts by weight of lithium oxide, 5 parts by weight of iron oxide, 3 parts by weight of titanium dioxide, 6 parts by weight of nano zirconium oxide and 10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:1.5; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1.5; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0025] Example 6: A high-nitrogen nickel-saving stainless steel protection slag and a preparation process thereof, comprising the following steps: Prepare components: 3 parts by weight of deoxidizer, 45 parts by weight of calcium oxide, 24 parts by weight of silicon dioxide, 14 parts by weight of aluminum oxide, 11 parts by weight of calcium fluoride, 4 parts by weight of magnesium oxide, 6 parts by weight of lithium oxide, 5 parts by weight of iron oxide, 3 parts by weight of titanium dioxide, 6 parts by weight of nano zirconium oxide and 10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:1.8; the mass ratio of the deoxidizer to the surfactant-modified nano-zirconia is 1:1.5; Dissolve germanium tetrachloride in an ethanol solvent to a mass concentration of 20 g / L, stir well, heat the solution to 78°C, and dropwise add a 0.1 M dilute hydrochloric acid solution to adjust the pH value to 5, then add N,N'-diphenylguanidine three times, and continue stirring for 6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with an ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer; The nano zirconium oxide is added to a hexadecyltrimethylammonium bromide solution with a molar concentration of 1M, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain a surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set to 110°C, and the water content is less than 2%. The dried protective slag is crushed, ground and sieved to obtain a protective slag with a particle size of 0.05-0.3mm.

[0026] Comparative Example 1: The method of Example 2 is adopted without adding a deoxidizer to the protective slag.

[0027] Comparative Example 2: The method of Example 2 was adopted, germanium tetrachloride was directly added, and N,N'-diphenylguanidine was not used.

[0028] Comparative Example 3: The method of Example 2 was adopted, N,N'-diphenylguanidine was directly added, and germanium tetrachloride was not used.

[0029] The present invention adopts a high nitrogen and nickel-saving stainless steel protection slag prepared by using a deoxidizer, wherein the performance index inspection items and inspection standards of the high nitrogen and nickel-saving stainless steel protection slag are as follows: Testing the deoxidation performance of continuous casting protection slag involves evaluating its ability to remove oxygen at high temperatures. Take 50g of protection slag as a test sample and put it into a preheated high-temperature furnace. Set the temperature of the high-temperature furnace to 1500℃ and introduce an oxygen environment for 30 minutes. After the oxidation treatment is completed, turn off the oxygen supply and take the sample out of the high-temperature furnace. Let it cool naturally to room temperature, weigh the sample before and after oxidation, and calculate the mass change. Calculate the oxidation weight gain rate based on the mass change to evaluate the deoxidation performance of the protection slag. Oxidation weight gain rate (W%) = (mass change of the sample before and after oxidation / initial mass) × 100%.

[0030] According to YB / T 185-2017 "Test Method for Viscosity of Continuous Casting Mold Slag", the rotation method is used to test the viscosity of continuous casting mold slag at 1300°C. The viscosity of continuous casting mold slag has an important influence on its performance in the continuous casting process. The viscosity determines the fluidity and stability of the mold slag. The mold slag with too high viscosity has poor fluidity, resulting in poor flow of liquid slag in the crystallizer, thereby affecting the stability of the continuous casting process.

[0031] According to the above standards, a high nitrogen nickel-saving stainless steel protection slag prepared in the above Examples 1-6 and Comparative Examples 1-3 was tested, and the obtained data are shown in Table 1: Table 1 Performance data of Examples 1-6 and Comparative Examples 1-3

[0032] The above data fully show that compared with Comparative Examples 1-2, Examples 1-3 can fully show the effect of the deoxidizer on the deoxidation performance of a high-nitrogen nickel-saving stainless steel protection slag.

[0033] Since the present invention adopts a deoxidizer to prepare a high-nitrogen nickel-saving stainless steel protection slag, the deoxidation performance of the protection slag is effectively improved by the deoxidizer, as follows: It can be seen from Examples 1-3 that as the deoxidizer content in the mold slag continues to increase, the deoxidation performance of the mold slag first increases and then decreases. This is because as the deoxidizer increases, the deoxidation effect is enhanced, and it can react with oxygen in the molten steel more effectively to prevent the molten steel from contacting oxygen in the air. Continuing to increase the deoxidizer content, a large amount of non-metallic inclusions will react with oxygen to form, which cannot float up and be discharged in time, causing pollution to the molten steel, thereby affecting the quality of the steel.

[0034] It can be seen from Examples 2-4 that as the contents of other components in the protective slag continue to change, the deoxidation performance of the protective slag remains basically unchanged. This is because the main function of the deoxidizer is deoxidation. When its content remains unchanged, small changes in other components within a certain range will not affect its deoxidation performance.

[0035] It can be seen from Examples 2, 5 and 6 that the deoxidation performance of the protective slag changes continuously with the continuous change of the component ratio in the deoxidizer. This is because the carbon dioxide and other gases produced by the decomposition of N,N'-diphenylguanidine at high temperature can promote the fluidity of the slag system and contribute to the uniform mixing within the slag system. With the increase of the component ratio in the deoxidizer, the coordination effect between N,N'-diphenylguanidine and the germanium element is enhanced, and the distance between the complexes is increased through electrostatic repulsion or steric hindrance effect, thereby improving the dispersibility of the deoxidizer in the protective slag, which enables the deoxidizer to be more evenly distributed in the protective slag to exert its deoxidation effect.

[0036] According to the above test experiments, the high-nitrogen nickel-saving stainless steel protection slag prepared according to Example 2 has the best performance, so Example 2 is taken as the best embodiment; By comparing Example 2 with Comparative Examples 1-3, it can be seen that: In comparative example 1, no deoxidizer is added to the protective slag, and the deoxidation performance of the protective slag is worse. This is because one of the main functions of the deoxidizer is to remove oxygen from the molten steel and reduce the formation of oxides. The lack of an effective deoxidizer will lead to an increase in inclusions in the molten steel, which will not only affect the quality of the steel, but also affect the purity of the protective slag.

[0037] In Comparative Example 2, germanium tetrachloride is directly added without using N,N'-diphenylguanidine. The deoxidation performance of the protective slag is worse. This is because after N,N'-diphenylguanidine is coordinated with the germanium element, the distance between the complexes can be increased by electrostatic repulsion or steric hindrance effect. On the one hand, it affects the dispersion of the germanium element in the protective slag. On the other hand, too fast deoxidation will lead to rapid aggregation of oxide inclusions, so the deoxidation performance of the protective slag is reduced.

[0038] In Comparative Example 3, N,N'-diphenylguanidine was directly added without using germanium tetrachloride. The deoxidation performance of the protective slag was worse. This was because the germanium element could effectively absorb oxygen in the molten steel and play a deoxidation role. The lack of effective deoxidizing components resulted in the inability to effectively remove oxygen in the molten steel. Although N,N'-diphenylguanidine could improve the fluidity of the slag system by decomposing and producing gas, it could not directly participate in the deoxidation reaction like germanium tetrachloride. Therefore, the deoxidation performance of the protective slag was reduced.

[0039] In summary, the deoxidizer prepared by the complex of germanium tetrachloride and N,N'-diphenylguanidine can not only absorb oxygen in the molten steel, but also utilize N,N'-diphenylguanidine to decompose and produce gas at high temperature, thereby improving the fluidity of the protective slag and the dispersion of the germanium element. At the same time, it can control the stable deoxidation efficiency of the deoxidizer, avoid the occurrence of over-deoxidation, and thus improve the surface quality of the ingot.

[0040] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A high nitrogen nickel-saving stainless steel protection slag, characterized in that: The invention comprises the following components: 1-5 parts by weight of a deoxidizer, 35-45 parts by weight of calcium oxide, 14-24 parts by weight of silicon dioxide, 6-14 parts by weight of aluminum oxide, 7-11 parts by weight of calcium fluoride, 2-4 parts by weight of magnesium oxide, 2-6 parts by weight of lithium oxide, 3-5 parts by weight of iron oxide, 1-3 parts by weight of titanium dioxide, 2-6 parts by weight of nano zirconium oxide and 2-10 parts by weight of hexadecyltrimethylammonium bromide; The deoxidizer is prepared from germanium tetrachloride and N,N'-diphenylguanidine in a mass ratio of 1:1.5-2.

2. The high-nitrogen nickel-saving stainless steel protection slag according to claim 1, characterized in that: The preparation method of the deoxidizer is as follows: Dissolve germanium tetrachloride in ethanol solvent, stir well, heat the solution to 75-78°C, add dilute hydrochloric acid solution to adjust the pH value, then add N,N'-diphenylguanidine three times, and continue stirring for 4-6 hours. After the reaction is completed, cool to room temperature, filter and separate the solid product, wash the solid product with ethanol solvent to remove unreacted raw materials and other impurities, and dry the product in a vacuum drying oven to constant weight to obtain a deoxidizer.

3. The high-nitrogen nickel-saving stainless steel protection slag according to claim 2, characterized in that: The mass concentration of the germanium tetrachloride solution is 20-40 g / L.

4. The high-nitrogen nickel-saving stainless steel protection slag according to claim 2, characterized in that: The molar concentration of the dilute hydrochloric acid solution is 0.1-0.5 M, and the pH of the solution is adjusted to 3-5.

5. A process for preparing a high-nitrogen nickel-saving stainless steel protective slag, used for preparing a high-nitrogen nickel-saving stainless steel protective slag as claimed in any one of claims 1 to 4, characterized in that: The steps include: The nano zirconium oxide is added to the hexadecyltrimethylammonium bromide solution, and after ultrasonic mixing, it is filtered and separated, washed with ethanol, and then vacuum dried to obtain the surfactant-modified nano zirconium oxide. The raw materials are firstly ground, and the deoxidizer, calcium oxide, silicon dioxide, aluminum oxide, calcium fluoride, magnesium oxide, lithium oxide, iron oxide, titanium dioxide and the surfactant-modified nano zirconium oxide are placed in a mixer. After fully stirring, water is added and stirring is continued until a uniform slurry with a certain fluidity is formed. The mixed raw materials are placed in an oven to evaporate the water, and the drying temperature is set at 100-110°C. The dried protective slag is crushed, ground and sieved to obtain the protective slag.

6. The process for preparing a high-nitrogen nickel-saving stainless steel protection slag according to claim 5, characterized in that: The particle size range of the raw material for preliminary grinding is 0.01-0.1 mm.

7. The process for preparing a high-nitrogen nickel-saving stainless steel protection slag according to claim 5, characterized in that: The molar concentration of the hexadecyltrimethylammonium bromide solution is 1-10M.

8. The process for preparing a high-nitrogen nickel-saving stainless steel protection slag according to claim 5, characterized in that: The mass ratio of the deoxidizer to the surfactant-modified nano-zirconium oxide is 1:1-1.

5.

9. The process for preparing a high-nitrogen nickel-saving stainless steel protection slag according to claim 5, characterized in that: The moisture content of the protective slag is less than 2%.

10. The process for preparing a high-nitrogen nickel-saving stainless steel protection slag according to claim 5, characterized in that: The particle size of the protective slag is 0.05-0.3 mm.